Daughters in the Deuterocanonical Books of the Old Testament - Wojciechowski, Michał (Verbum Vitae, 2020)
The instances where daughters are mentioned in the Greek books of the Old Testament are not numerous. They are interesting, however, and deserving of exegesis and interpretation. In Tobit and Ben Sira their relationship to fathers are stressed and this aspect is of importance, whether those relationships are good or strained. If the texts are compared with the Hebrew Bible, more light is thrown on the personalities of the daughters, and they are valued more highly. Some influence of the Greek civilization can be presupposed here. A link with the Mediterranean culture of honor and shame can also be traced, especially in Ben Sira.